Analysis of regional tax potential in Toba Regency: A Study on the potential of hotel and restaurant taxes in Toba Regency - Sitorus, Laurenza; Tambunan, Frederik Halomoan (Educoretax, 2025)
Compared to other regencies and cities in North Sumatra, the performance of Toba Regency's Local Revenue (PAD) is still below the average (6.51% compared to 9.35%). As a tourist destination, Toba Regency has significant potential to enhance local taxes, particularly hotel and restaurant taxes. Data from the past nine years shows a consistent increase in both hotel and restaurant taxes in Toba Regency. This indicates that the potential for these taxes can still be optimized further. This research employs both quantitative and qualitative methods, using a macro and micro approach. The macro approach involves calculating the Compound Annual Growth Rate (CAGR), while the micro approach uses calculations based on field survey data. The data sources include primary data from taxpayer surveys and secondary data, which consists of historical information from the BPPD of Toba Regency, the Central Statistics Agency, the Provincial Government of North Sumatra, and the DJPK Ministry of Finance. The findings of this study show that the actual revenue from hotel and restaurant taxes in Toba Regency is still below the potential tax value.